LONG-TERM OUTCOMES OF SPINKTER-SPARING SURGERIES IN MID- AND LOWER AMPULLARY RECTAL CANCER: QUALITY OF LIFE AND SURVIVAL OF PATIENTS - A. A. Medvednikov; A. V. Shelekhov; V. V. Dvornichenko; R. I. Rasulov; S. M. Plenkin; N. V. Popova; A. G. Zakharov; N. A. Nikolaeva; S. I. Radostev; A. A. Litvintsev (Сибирский онкологический журнал, 2020)
The purpose of the study was to comparatively analyze surgical outcomes in patients with histologically proven rectal cancer. Material and methods. From 1999 to 2012, 174 patients with histologically proven rectal cancer underwent abdominal-anal resection of the rectum with bringing down the sigmoid colon into the anal canal and sphincter-preserving low intra-abdominal resection of the rectum with coloanal anastomosis.Results. Two groups of patients were studied: the main group (sphincter-preserving low intra-abdominal rectal resection) and the control group (abdominal-anal resection of the rectum). The 5-year survival rates and quality of life of the patients (Wexner scale) were compared. Improvement in fecal retention function was observed in both groups a year after surgery. However, 17 patients in the control group (25 %) had unsatisfactory function of the closure apparatus (11–20 points on the Wexner scale), sharply limiting their social activity and requiring the use of anal tampons. Fecal incontinence was observed in 95% of the control group patients 1 year after surgery. A significant improvement in the quality of life associated with adequate sphincter function was found in the main group of patients. In 40 out of 88 patients who had survived 1 year (45 %), no significant violations of the closure function were revealed. The remaining patients had symptoms of fecal incontinence or inability to control bowel movements for a long time (less than 10 points on the Wexner scale). Conclusion. The use of low anterior rectal resection with coloanal anastomosis in the surgical treatment of cancer, significantly improves the patient’s quality of life without compromising the radicality and safety of treatment.